Diseño de un plan financiero para incrementar la rentabilidad de la Biotienda Randi de Zapotillo en la provincia de Loja - Jiménez Sánchez, Janeth Jazmin (2024)
The content of this research work is related to the topic: Design of a financial plan to increase the profitability of the Randi de Zapotillo biostore in the province of Loja; To study the two variables, a mixed approach was used, with a non-experimental design. The analytical, descriptive, and synthetic methods were used. With regard to obtaining the information, the documentary technique was used, the information was provided from the records managed by the Biotienda Randi, which served to prepare the financial statements for subsequent analysis and to them the formulas of the financial indicators that later allowed financial planning to be established to improve business profitability. Once the data was obtained, it was possible to conclude that, in the internal environment, the Randi Biostore does not have an organizational culture that allows it to increase its sales and position itself in the southern region of Ecuador; They do not have process management, continuous improvement, they do not have financial statements and for the financial diagnosis it was necessary to design it based on the monthly reports that they maintain as the only information. There is no budget planning; The management of human, technological and marketing talent is not managed.